Synthesis and rheological characterization of linear and star-shaped polydimethylsiloxanes - Ressia, Jorge Aníbal (2001)
Linear polydimethylsiloxanes (PDMS) and 3‐ and 4‐arm star‐shaped PDMS of narrow molecular weight distribution (MWD) have been synthesized by anionic polymerization. The MWD was obtained by Size Exclusion Chromatography (SEC). Some of the anionically synthesized PDMS showed a relative broad MWD, especially when they were terminated after 3 or more days of reaction. In order to analyze the influence of the extent of reaction on the MWD, a polymerization with sample extractions at different conversions was performed. The MWD of the polymers synthesized at different extents of reaction were studied from a statistical point of view. Linear viscoelastic parameters of the synthesized polymers, such as storage (G′) and loss (G″) moduli, were obtained at different temperatures as functions of frequency (ω). Zero shear rate viscosity (η0) was calculated from the data obtained in the terminal relaxation zone. The molecular weight dependence of η0 shows a good agreement with classical models. Preliminary results obtained from the star polymers suggest an exponential increase in η0 with the number of entanglements per arm.